2001
DOI: 10.1292/jvms.63.163
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Aortic Elastic Fibers in Copper-Deficient Sika Deer(Cervus nippon Temminck).

Abstract: ABSTRACT. Light microscopic and transmission and scanning electron microscopic observations were performed on the aortas of two 4-and 6-year-old deer affected with cervine ataxia and two 6-month-and 4-year-old healthy deer. Examination of the aortas from affected deer by transmission electron microscopy revealed the absence of distinct elastic laminae in the internal elastic lamina and tunica media, but discontinuous and irregular clumps of elastin were present. Scanning electron microscopy disclosed immature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…In the rofecoxib-treated group, the elastic lamellae in the tunica media of the thoracic aorta were focally disrupted, resulting in a greater degree of branching than those in the control aorta. These observations are similar to the findings in animals and humans under conditions inhibiting cross-linking of elastin fibers (Herd and Orbison, 1966;Andrews et al, 1975;Hashimoto et al, 1981;Light et al, 1986;Yoshikawa et al, 2001). In our previous report (Oitate et al, 2006), we demonstrated that the radioactivity from [ 14 C]rofecoxib was localized on the elastic fibers of rat aortas by microautoradiography and that the accumulation of radioactivity in the aortas increased in a dosefrequency-dependent manner.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the rofecoxib-treated group, the elastic lamellae in the tunica media of the thoracic aorta were focally disrupted, resulting in a greater degree of branching than those in the control aorta. These observations are similar to the findings in animals and humans under conditions inhibiting cross-linking of elastin fibers (Herd and Orbison, 1966;Andrews et al, 1975;Hashimoto et al, 1981;Light et al, 1986;Yoshikawa et al, 2001). In our previous report (Oitate et al, 2006), we demonstrated that the radioactivity from [ 14 C]rofecoxib was localized on the elastic fibers of rat aortas by microautoradiography and that the accumulation of radioactivity in the aortas increased in a dosefrequency-dependent manner.…”
Section: Discussionsupporting
confidence: 87%
“…7A). It has been demonstrated that the prevention of this cross-linking in elastin causes serious lesions of connective tissues in animals and humans (Herd and Orbison, 1966;Andrews et al, 1975;Hashimoto et al, 1981;Junker et al, 1982;Light et al, 1986;Yoshikawa et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSION LOX initiates the formation of the lysine-derived crosslinks in tropoelastin, resulting in the mechanical stability of elastic fibers. A deficiency in enzyme activity of LOX resulting from treatment with BAPN, 20) copper deficient 21) or genetic modification 12) leads to aortic aneurysms and cardiovascular dysfunction. Previously, we and others found that inhibition of LOX enzyme activity by BAPN leads to loss-of-elastin assembly.…”
Section: )mentioning
confidence: 99%
“…10,15 Similar structural changes have been observed in wild ruminants. 27 The histopathologic changes observed in human aortic aneurysms comprise elastic fiber fragmentation, accumulation of ground substance, loss of smooth muscle cells, and fibrosis within the arterial media. 13,22 Historically, these histologic features have been considered aneurysm specific, but further investigations revealed the occurrence of morphologically identical changes in the normal aging human aorta, albeit to a lesser extent compared with those described in aneurysms.…”
mentioning
confidence: 99%